An implantable device for neuropsychiatric rehabilitation by chronic deep brain stimulation in freely moving rats - Liu, Hongyu (Neuroreport, 2017)
Successful practice of clinical deep brain stimulation (DBS) calls for basic research on the mechanisms and explorations of new indications in animals. In the article, a new implantable, single-channel, low-power miniature device is proposed, which may transmit pulses chronically into the brain nucleus of freely moving rats. The DBS system consists of an implantable pulse generator (IPG), a bipolar electrode, and an external programmer. The IPG circuit module is assembled as a 20-mm diameter circular board and fixed on a rat’s skull together with an electrode and battery. The rigid electrode may make its fabrication and implantation more easy. The external programmer is designed for bidirectional communication with the IPG by a telecontrol transceiver and adjusts stimulation parameters. A biological validation was performed in which the effects of electrical stimulation in brain nucleus accumbens were detected. The programmed parameters were accurate, implant steady, and power sufficient to allow stimulation for more than 3 months. The larger area of the electrode tip provided a moderate current or charge density and minimized the damage from electrochemistry and pyroelectricity. The rats implanted with the device showed a reduction in morphine-induced conditioned place preference after high-frequency stimulation. In conclusion, the DBS device is based on the criteria of simple technology, minimal invasion, low cost, small in size, light-weight, and wireless controlled. This shows that our DBS device is appropriate and can be used for preclinical studies, indicating its potential utility in the therapy and rehabilitation of neuropsychiatric disorders.